Legalization of Public Documents Through Apostille: A Legal Reform in Public Services - Tan, Winsherly; Patros, Asmin; Hutauruk, Rufinus Hotmaulana (Law and Human Rights Research and Development Agency, 2023)
Indonesia is a country that has the objective of ensuring the welfare of its citizens. One effective way to achieve prosperity for its citizens is by implementing excellent public services, especially when it comes to the fulfillment of rights concerning the legalization of public documents. Therefore, this study is aimed to analyze the application of the Apostille convention in the legalization of public documents, and to investigate the changes in the law of public services related to the legalization of documents after the Apostille enactment. This legal study is categorized as a type of doctrinal analysis. Specifically, it is descriptive and analytical. Juridical and theoretical foundations were used for data analysis and the theoretical basis employed was the Theory of Legal Reform. The finding is consistent with the principles of the Legal Reform Theory. Legalization of public documents has undergone legal reform because legalization of public documents can be done online and in a short time. This shows that law, as a means of reform, has been realized because it has met the needs of society for the public. Despite the enhancement of public services, several aspects require careful consideration and improvement. This includes establishing effective cooperation with the Regional Office of Law and Human Rights, which acted as a liaison for Apostille services at the regional level. Additionally, the Regional Office of Law and Human Rights assume a pivotal role in overseeing the printing of certificates to ensure accessibility for the public.